Analisis Pengelolaan Sedekah Anak Yatim (Studi Kasus Di Lembaga Amil Zakat Yatim Mandiri Medan) - Fadilah, Fanny; Lestari, Annio Indah; Bi Rahmani, Nur Ahmadi (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Yatim Mandiri Foundation is a ziswaf management institution, (Zakat, Infaq, Sadaqah). In kinerja has sanggar genius program free of charge for orphans. This study aims to determine, first, how the management system of Laz Yatim Mandiri Medan alms in the Sanggar Genius program, second, the extent to which the management of alms in encouraging the sanggar genius program, third, the constraints in the management of alms in the Sanggar Genius program. This research was conducted at the Amil Zakat Yatim Mandiri Medan institution. The research approach is descriptive qualitative with data collection that is using observation techniques, interviews and documentation. The results of this study indicate that first Laz Yatim Mandiri Medan has collected, managed, and distributed and supervised alms funds, Laz Yatim Mandiri Medan supervises the management of alms funds in accordance with their purpose, function and designation to remain in accordance with SOP. All expenses and reporting are well recorded, both Sanggar Genius programs are very helpful in encouraging the education of orphans, from teaching and learning activities, educational facilities, genius teachers, and making them more productive in the future, with the fulfillment of all education. the three constraints in the management of alms in the sanggar genius program include, budget management activities of financial resources in the Sanggar Genius program has not used information systems (applications), Sanggar Genius program still relies on one donor, organizing for the Sanggar Genius program has not been organized with structured so it is difficult to form or divide a smaller activities. And socialization in the community is still 65% seen from the recruitment of assisted children in 2021, only 130 targets recruit a maximum of 200 assisted children, with that less than 70 children from the target set by Laz Yatim Mandiri Medan